2017
DOI: 10.1590/s0004-2803.201700000-18
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Combination With Triple Therapy Regimes Ameliorates Oxidative Stress and Histopathologic Changes in Chronic Gastritis-Associated Helicobacter Pylori Infection

Abstract: -Background -Helicobacter pylori (H. pylori) gastric infection is a main cause of inflammatory changes and gastric cancers. Objective -The aim of this study was finding the effects of curcumin on oxidative stress and histological changes in chronic gastritis associated with H. pylori. Me thods -In a randomized clinical trial, patients were divided into two groups: a standard triple therapy group and triple therapy with curcumin group. Endoscopic and histological examinations were measured for all patients befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
1
43
0
2
Order By: Relevance
“…Curcumin can also inhibit the production of many proinflammatory cytokines by inhibiting the activity of inducible NOS, which can alleviate the inflammatory reaction of mice with multidrug resistance gene deficiency, alleviate the development of colitis induced by sodium dextran sulfate, and inhibit the production of many proinflammatory cytokines [6] . NO free radicals and superoxide anions were effectively eliminated, and oxidative stress and acute gastric injury were alleviated [7] . The results of this study are similar to those of the above studies.In conclusion, curcumin may inhibit NO production to improve gastric emptying by inhibiting the activity of inducible NOS in gastric tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can also inhibit the production of many proinflammatory cytokines by inhibiting the activity of inducible NOS, which can alleviate the inflammatory reaction of mice with multidrug resistance gene deficiency, alleviate the development of colitis induced by sodium dextran sulfate, and inhibit the production of many proinflammatory cytokines [6] . NO free radicals and superoxide anions were effectively eliminated, and oxidative stress and acute gastric injury were alleviated [7] . The results of this study are similar to those of the above studies.In conclusion, curcumin may inhibit NO production to improve gastric emptying by inhibiting the activity of inducible NOS in gastric tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Combining of phytomedicine with standard medicine may offer effective H. pylori treatment. Judaki et al reported that addition of a turmeric extract (curcumin) to the standard triple therapy significantly increased the eradication rate of H. pylori and decreased oxidative damage to DNA (Judaki et al 2017). Treatment with curcumin reduced the number of bacteria colonizing gastric mucosa and reduced the activity of lipid peroxidases and urease in H. pylori infected mice (Kwiecien et al 2019).…”
Section: Phytomedicine In the Treatment Of H Pylorimentioning
confidence: 99%
“…A study from Africa suggests that the methanol extract of Bryophyllum pinnatum , a plant known for its antioxidant properties, could inhibit H. pylori growth, and may also act as an antioxidant to protect gastric mucosa against reactive oxygen species . A study from Iran demonstrated reduced endoscopic scores of inflammation and increased H. pylori eradication rates with the addition of curcumin (a turmeric extract) to standard triple therapy . An Egyptian group evaluated eradication rates with nitazoxanide, an anti‐infective drug with demonstrated activity against protozoa and anaerobic bacteria but also H. pylori .…”
Section: Novel Therapiesmentioning
confidence: 99%